Fest (2018)
Muscular disuse-atrophy affects a great amount of people of different backgrounds. For this reason, we hav designed an EMS device to be applied during the immobilization to decrease the appeareance of musucular atrophy. In this work, the design and the proof of concept of the device can be found, aswell as the business plan.--Tomado del Formato de Documento de Grado.